Programação em Python no ambiente educacional: uma proposta de ensino de modelagens algébricas - Matias, Marcos José (2024)
This study investigates how programming in Python can assist in learning algebraic modeling. The central problem addressed is the difficulty of 8th-grade students at a rural school in the interior of São Paulo in formulating algebraic models to solve everyday mathematical problems. The objectives of this work were to develop the students’ ability to recognize, generalize, and create algebraic expressions to solve problem situations. The methodology included 10 Python programming lessons with various activities designed to stimulate the development of algebraic skills. The results, obtained through process based assessments, demonstrated a significant improvement in the students’ ability to solve problems algebraically. This study contributes to highlighting the importance of computer programming in Mathematics education from the early years. Future research may further explore the impact of computer programming on Mathematics education in Basic Education.